2021
DOI: 10.1186/s12879-021-05997-w
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescriptions for children younger than 5 years with acute upper respiratory infections in China: a retrospective nationwide claims database study

Abstract: Background In China, there were few studies to estimate antibiotic use for children with upper respiratory infections at the national level. The aim of this study was to describe the antibiotic prescribing practice for children aged < 5 years old with upper respiratory infections (URIs) using a nationwide claims database. Methods This was a retrospective cross-sectional study using a sampled database from the China Health Insurance Research Asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…In our study, the rate of antibiotic prescriptions was the highest (48.0%) in outpatients aged 3 to 6 and the lowest (6.0%) in adolescents. This distribution confirms the results of numerous previous studies, that showed the predominance of antibiotic use in preschool children [4][5]9,25].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, the rate of antibiotic prescriptions was the highest (48.0%) in outpatients aged 3 to 6 and the lowest (6.0%) in adolescents. This distribution confirms the results of numerous previous studies, that showed the predominance of antibiotic use in preschool children [4][5]9,25].…”
Section: Discussionsupporting
confidence: 91%
“…This fact, at least in part, explains the predominance of penicillins in the United States and some European countries (the Netherlands, Denmark, Italy, and Spain) [1,5,[26][27]. In China, cephalosporins account for the majority of antibiotic prescriptions for this purpose [25,28].…”
Section: Discussionmentioning
confidence: 99%
“…Upper respiratory infection (URTI) was another empirically diagnosed condition in the current study, and antibiotic prescriptions among patients with URTI were almost double those with other disease conditions. This is comparatively higher than that in another study in Indonesia on the use of antibiotics in URTI, where 44% of the cases attended were prescribed antibiotics [ 35 ]; in another study involving antibiotic prescriptions for URTI in children under the age of five in China, 27.5% of all the 92,821 consultations of children between 3 to <5 years were prescribed antibiotics, accounting for over 60% of all the antibiotic prescriptions [ 36 ]. Additionally, in a study on antibiotic prescribing for URTI outpatients during influenza seasons involving 14,947 outpatients, over 40% were prescribed antibiotics, 41% of whom had conditions not requiring antibiotic therapy [ 37 ].…”
Section: Discussionmentioning
confidence: 75%
“…12 Higher rates of antibiotic prescribing with an inappropriate selection of antibacterial doses are also observed in other parts of Asian subcontinent too. A nationwide retrospective cross-sectional study conducted in China by Xue et al 13 reporting the antibiotic prescribing practices in children aged less than 5 years with URTIs demonstrated that 27.1% were prescribed injectable antibiotics and that too at a higher dose. This trend was particularly noted in underprivileged areas.…”
Section: Discussionmentioning
confidence: 99%